2015
DOI: 10.3329/bjsir.v50i4.25836
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of transesterification of Madhuca Indica oil over modified zeolites: biodiesel synthesis

Abstract: In this article production of biodiesel from Madhuca indica oil (MI-oil) containing high % of free fatty acids (FFA) by transesterification process with methanol over basic zeolites such as NaY loaded with 5-25% KOH is presented. The zeolites were characterized by PXRD, BET and CO 2 -TPD methods prior to their catalytic activity studies. Optimization of reaction conditions for transesterification was conducted in order to get highest possible yield of biodiesel. 1HNMR and FTIR analysis confirms the conversion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Zeolites have been widely used as a carrier in biodiesel production in the past decade [75][76][77][78]. Zeolites with specific pore structure and surface hydrophobicity can be modified depending on the substrate's polarity and size, and hence, molecules with diameters smaller than the proper catalyst size can enter the cavity and diffuse [38].…”
Section: Supported and Loaded Cao Catalystsmentioning
confidence: 99%
“…Zeolites have been widely used as a carrier in biodiesel production in the past decade [75][76][77][78]. Zeolites with specific pore structure and surface hydrophobicity can be modified depending on the substrate's polarity and size, and hence, molecules with diameters smaller than the proper catalyst size can enter the cavity and diffuse [38].…”
Section: Supported and Loaded Cao Catalystsmentioning
confidence: 99%
“…Another group has (Pratap et al, 2015) reported the use of NaY and KOH/NaY zeolites catalyst in trans-esterification of Madhuca indica oil. These zeolites have attained a conversion efficiency of 98.9%.…”
Section: Zeolite Based Nanocatalystmentioning
confidence: 99%
“…As these catalysts are recycled and reused several times, they can be easily activated by washing with methanol followed by calcination in a muffle furnace for a given period of time. Due to the presence of large basic sites, its catalytic activity has increased to a greater extent (Pratap et al, 2015). However, synthesizing nanocatalysts with zeolite plays an important role in achieving maximum conversion, recyclability, and reusability of the catalyst involved in trans-esterification reaction.…”
Section: Zeolite Based Nanocatalystmentioning
confidence: 99%
“…This has a continuing impact on the costs of the biodiesel production process. Various types of homogeneous and heterogeneous catalysts have been widely studied such as NaOH/KOH [6], 4dodecyl benzene sulfonic acid [7], La2O3 [8], zeolite [9], [10], CaO [11], [12] and still much more. Fly ash has the potential as a catalyst for the manufacture of biodiesel.…”
Section: Introductionmentioning
confidence: 99%